2018
DOI: 10.1016/j.bjm.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Archaea diversity in vegetation gradients from the Brazilian Cerrado

Abstract: We used 16S rRNA sequencing to assess the archaeal communities across a gradient of Cerrado. The archaeal communities differed across the gradient. Crenarcheota was the most abundant phyla, with Nitrosphaerales and NRPJ as the predominant classes. Euryachaeota was also found across the Cerrado gradient, including the classes Metanocellales and Methanomassiliicoccaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
2
7
0
3
Order By: Relevance
“…As expected, Thaumarchaeota and Euryarchaeota were the most abundant phyla found in soils with application of CTS (Fig. 1), which corroborates previous studies that reported these phyla as dominant in several soils 1315 . Interestingly, the phylum Thaumarchaeota was dominant in all samples and matches the fact that this phylum is found in high abundance in both marine and soils environments 16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…As expected, Thaumarchaeota and Euryarchaeota were the most abundant phyla found in soils with application of CTS (Fig. 1), which corroborates previous studies that reported these phyla as dominant in several soils 1315 . Interestingly, the phylum Thaumarchaeota was dominant in all samples and matches the fact that this phylum is found in high abundance in both marine and soils environments 16,17 .…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with patterns observed for other microbiome components, i.e. bacteria 13 , 15 , 18 , archaea 16 and fungi 17 , 18 . These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone.…”
Section: Discussionsupporting
confidence: 90%
“…These patterns can be attributed to abiotic differences, such as lower fertility and soil moisture, but higher acidity and soil temperature, in the grass compared to the tree zone. Abiotic differences were shown to drive above-ground plant community-dynamics across the Cerrado 39 , 40 , and therefore likely also belowground communities 13 , 16 , 17 . In line with other studies, we show that a combination of multiple abiotic factors drive protist communities, with soil moisture being the principle factor 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations